Analisis Perda Kabupaten Mukomuko Nomor 5 Tahun 2016 Tentang Berpakaian Muslim dan Muslimah Bagi Siswa Berdasarkan Teori Peraturan Perundang-Undangan - Robiatul Adawiyah; Lita Tyesta Addy Listya Wardhani (Law Department, Sharia and Law Faculty., 2020)
In the context of implementing autonomy and co-administration, local governments have right to make regional regulations. This authority opens the opportunity for the emergence of regional regulations with Islamic nuances, for example the Mukomuko Regency Regional Regulation Number 5 of 2016. This raises pros and cons among the community. Therefore, this is very important to be studied comprehensively. The research method used is normative. As for the issues raised: first, What is the content of the provisions of the Mukomuko District Regulation Number 5 of 2016? second, What is the Regional Regulation of Mukomuko Regency Number 5 of 2016 based on the theory of statutory regulations? Based on research results, that the regional regulation is a sharia-based regional regulation that regulates moeslim dress. In the formation of regulations, including at the regional level, it must not conflict with Pancasila and also the content material principles in Law of PPPU. When referring to Guidelines for Legal Analysis and Evaluation Number PHN-01.HN.01.03 of 2019 which is result of breakdown of Pancasila and Law of PPPU, it is found that based on the variables and indicators of assessing values of Pancasila, this is contrary to the variable of plowing, humanity, nationality, Diversity in Unity, justice, equality in law and government, and legal order and certainty. And type of statutory regulation, namely this regional regulation is not appropriate. This regional regulation also creates disharmony in regulations.